Ocean model skill assessment in the NW Mediterranean using multi-sensor data. Issue 2 (2nd July 2016) - Lorente, Pablo; Piedracoba, Silvia; Sotillo, Marcos García; Aznar, Roland; Amo-Baladrón, Arancha; Pascual, Álvaro; Soto-Navarro, Javier; Álvarez-Fanjul, Enrique
ABSTRACT: This paper showcases the one year-long (2014) multi-parameter skill assessment of Iberia-Biscay-Ireland (IBI) operational ocean forecasting system. The investigation is focused on a specific subdomain in the Northwestern Mediterranean where several observational networks encompassing both in situ and remote sensing instruments are available. This region is relevant since it includes two harbours and a marine protected area, the Ebro River Delta. Class-1 and class-2 skill metrics are used in concert to quantitatively evaluate the quality of hourly IBI surface fields. The impact of riverine discharges on the coastal circulation is investigated by comparing the signal of the Ebro River freshwater outflow in both observed (high-frequency radar (HFR)) and modelled (IBI) current maps. The ability of the HFR and IBI to detect the presence of coastal eddies is also qualitatively estimated by calculating surface vorticity maps. According to the results, basic circulation features are statistically reproduced by IBI in reference to mean and variance, despite some model drawbacks in terms of reduced energy content in surface currents. IBI has proven to be a robust model solution in the study area, able to act as a consistent large-scale 'father' system in future downscaling approaches by providing coherent open boundary conditions to nested high-resolution coastal models.